Efficiency Versus Equity in the Provision of In-Kind Benefits: Evidence from Cost Containment in the California WIC Program - Katherine Meckel; Maya Rossin-Slater; Lindsey Uniat (Institute of Labor Economics (IZA), 2020)
The government often contracts with private firms to deliver in-kind safety net benefits. These public-private partnerships generate agency problems that could increase costs, but cost-containment reforms may discourage firm participation. We study a 2012 reform of California's Special Supplemental Nutrition Program for Women, Infants, and Children that reduced the number of small vendors. We show that within-ZIP-code access to small vendors increases take-up among first-time and foreign-born mothers, suggesting that small vendors are distinctly effective at lowering take-up barriers among women with high program learning costs. Thus, cost containment reforms may have unintended consequences of inequitably reducing program access.
Keywords: H40; I18; I38; 330; WIC program; benefit take-up; in-kind transfers; cost containment